Edema agudo de pulmão como manifestação de embolia pulmonar: relato de caso - Polegato, Bertha Furlan [UNESP]; Minicucci, Marcos Ferreira [UNESP]; Matsubara, Luiz Shiguero [UNESP]; Inoue, Roberto Minoru Tani [UNESP]; Azevedo, Paula Schimidit [UNESP]; Zornoff, Leonardo Antonio Mamede [UNESP]; Ribeiro, Sérgio Marrone [UNESP]; Paiva, Sergio Alberto Rupp de [UNESP]; Okoshi, Marina Politi [UNESP] (My University, 2011)
Background and objectives: Pulmonary embolism presenting as pulmonary edema is an uncommon condition in patients without left ventricular systolic dysfunction. Physiopathology of non cardiac pulmonary edema associated with pulmonary embolism is not entirely clear. Blood overflow in parenchymal areas with patent pulmonary arteries and increased capillary permeability are possible mechanisms involved. We report the case of a patient with acute pulmonary edema caused by pulmonary embolism and infarction. Case report: Female patient, 67 year-old, referred to our hospital with sudden onset dyspnea and orthopnea. Chest radiography revealed bilateral pulmonary edema and computed tomographic arteriography detected pulmonary embolism associated with areas of pulmonary infarction. Conclusion: This report reinforces that pulmonary embolism should be considered as a differential diagnosis in acute pulmonary edema with unknown etiology.

Justificativa e objetivos: Apresentação clínica de embolia pulmonar como edema agudo de pulmão é incomum em pacientes sem disfunção sistólica do ventrículo esquerdo. A fisiopatologia do edema agudo de pulmão não cardiogênico associado à embolia pulmonar não está claramente esclarecida. Possíveis mecanismos como aumento da permeabilidade capilar e hiperfluxo em áreas pulmonares com artérias não ocluídas parecem estar envolvidos. O objetivo deste estudo foi relatar um caso de paciente admitida com edema agudo de pulmão causado por embolia e infarto pulmonar. Relato do caso: Paciente do sexo feminino, 67 anos, encaminhada à Sala de Emergência com dispneia súbita e ortopneia. À investigação complementar, radiografia de tó- rax mostrou edema pulmonar bilateral e a angiotomografia computadorizada revelou embolia associada a áreas de infarto pulmonar. Conclusão: O relato reforça a importância de incluir embolia pulmonar como um dos diagnósticos diferenciais em pacientes com edema agudo de pulmão de etiologia obscura.
Pulmonary embolism and infarction presenting as acute pulmonary edema: case report
Keywords: Pulmonary edema; Pulmonary embolism; Thrombosis; Edema agudo de pulmão; Embolia pulmonar; Trombose